Synthesis and Characterization of Some New Heterocyclic Selenium Compounds On3,5 – Naphtho-1-Selenocyclo hexane - Al-Hazam , Hanan Abdul Galeel; Faily, Naeem Taki; Alwaaly, Ahmed Ali; Hassan, Attard F. (Al-Mukhtar Journal of Sciences, 2010)
A new series of heterocyclic derivatives from 3, 5 – naphtho 1- seleno cyclohexane have been prepared (i.e.: C12 H10 SeX; X=CL Br, I and C12H10 SeRX; R=CH3; X=I) The new compounds were characterized by elemental analysis, IR, H1NMR and molar conductance. Conductivity measurements of these compounds in DMSO solution indicated that they are behave as week electrolytes.